Towards Radiopharmaceutical Synthesis Using Fluorous Chemistry - Dorff, Peter Norman (My University, 2002)
Nuclear medicine requires the use of radio labelled pharmaceuticals in order to carry out imaging and therapeutic protocols.1 Unfortunately, traditional radiolabelling approaches used in radiopharmaceutical synthesis often generate multiple products, which require exhaustive HPLC purification prior to use.2 Chromatographic purification reduces radiochemical yields, increases exposure, and can, in certain cases, preclude the use of shorter-lived isotopes.
In light of the limitations of current radio labelling methods, we endeavored to develop a versatile and efficient radiolabelling strategy that would avoid the need for HPLC purification. To this end, the compounds to be labelled were first bound to a highly fluorinated stannylated precursor, which, when reacted with a radiohalogen, generated the corresponding radiolabelled compound. Unlike other halodestannylation reactions, however, the radiolabelled compound could be isolated from the stannylated precursor by elution through a fluorous Sep-Pak.
As a model system, tris(perfluorohexylethyl)tin-3-benzoic acid (1), was synthesised and labelled. Compound 1 was prepared through a novel reaction which involved treatment of bromotris[(2-perfluorohexyl)ethyl]tin with the organozinc reagent 3-(ethoxycarbonyl)phenylzinc. Reaction of compound 1 with [18F]F2, followed by fluorous Sep-Pak purification, generated the corresponding labelled 3-[18F]fluorobenzoic acid in 27 min, in 30% radiochemical yield, and having a specific activity of 1966 mCi/mol. Alternatively, reaction of compound 1 with Na125I provided the corresponding product, 3-[125I[iodobenzoic acid, in <1 hr, in 75% radiochemical yield, and greater than 99% radiochemical purity. Prior tests clearly showed that any excess or unreacted substrate was fully removed from the product using a fluorous Sep-Pak.
In addition to the initial validation studies, new synthetic methods were developed as a means of preparing more complex "fluorous" substrates. A coupling methodology was developed which permitted synthesis of a fluorous "tagged" benzamide, through reaction of 1 in the presence of HBTU with N,N-dimethylethylenendiamine. Subsequent labelling using F2 and I2 has been shown to generate the corresponding labelled benzamides, which are important agents for imaging melanoma and dopamine receptors.3 Another relevant radiopharmaceutical precursor, tris[(2-perfluorohexyl)ethyl]tin-3-benzylamine (2), was synthesized though reaction of bromotris[(2-perfluorohexyl)ethyl]tin with 1-(3-bromobenzyl)-2,2,5,5-tetramethyl-1,2,5-azadisilolidine. Compound 2 was successfully coupled to the chemotactic peptide, GFLM(f), and the product subsequently labelled with iodine. Compound 2 was also used to prepare the corresponding benzylguanidine (3), an important precursor to m-iodobenzylguanidine, which is used for imaging and therapy of neural crest tumors.4 Initial labelling results show that reaction of 3 with NaI and an oxidant generates the corresponding labelled m-iodobenzylguanidine.
Results suggest that the fluorous synthesis method will offer several advantages over traditional radiolabelling strategies. The radiolabelled products are generated in high yield, through rapid and facile reactions that avoid the need for HPLC purification.
Keywords: radiopharmaceutical, synthesis, fluorous, chemistry, therapeutic